Madison's Ratchet: ambition counteracting ambition and the aggregation of political, managerial, and legal controls over federal administration - Rosenbloom, David H.; Newbold, Stephanie P. (2018)
In Federalist 47 and 51, James Madison contended that the accumulation of legislative, executive, and judicial powers in the hands of one body or person would produce tyranny. He explained that one defense against such tyranny was to make (3z(Bambition . . . counteract ambition(3y (Bby giving each of the three constitutional branches of the federal government the (3z(Bmeans,(3y z(Bmotives,(3y (Band wherewithal to (3z(Bresist encroachments(3y (Bon their powers by another. However, after the development of the contemporary administrative state in the 1930s, rather than serving as a check against encroachments alone, the process of ambition counteracting ambition prompts each branch to develop its own set of controls over federal agencies without necessarily trenching on the powers of the other branches. (3z(BMadison$1 (Bs Ratchet(3y (Bis the tendency for these controls overwhelmingly to aggregate and thereby vastly complicate federal administration. - Reproduced.s
Keywords: Political parties - USA